Stability analysis of symbiotic bioenergy parks - Ng, Rex T.L. (Animo Repository, 2014)
In this work, a novel stability analysis for symbiotic bioenergy park is introduced. The concept of incremental investment return (IIR) analysis is adapted to determine the distribution of the savings associated with the additional investment required for implementation of industrial symbiosis (IS) scheme. Deviation from the ideal status of IS system can be obtained by determining the asymmetric distribution coefficient of each processing plant. An IS system is stable for as long as no partner bears a disproportionate share of additional investment costs relative to benefits gained from cooperation. To ensure a stable IS system, the asymmetric distribution coefficient must be bounded within maximum and minimum limits that can be determined based on the individual plants' requirements or company policies. In case where the asymmetric distribution coefficient of one of the processing plants falls outside of the predefined limits, the symbiotic bioenergy park is not stable, and the proposed IS scheme cannot be implemented. A palm-based symbiotic bioenergy park case study is solved to illustrate the proposed approach. Copyright © 2014, AIDIC Servizi S.r.l.